The endocannabinoid system in the brain undergoes long-lasting changes following neuropathic pain - Ming Zhang; Tao Wang; Fancheng Meng; Mengyang Jiang; Shengxi Wu; Hui Xu (iScience)
Summary: The endocannabinoid system (ECS), which is composed of endocannabinoids (eCBs), cannabinoid receptors (CBRs), and associated signaling molecules, has been identified within the brain. In neuropathic pain animal models and patients, long-lasting alterations in the ECS have been observed. These changes of neurons and glial cells in the ECS contribute to the modulation of neuropathic pain. Intervention strategies such as the activation of CBRs, the enhancement of hydrolytic enzyme function, and the inhibition of synthetizing enzymes typically alleviate neuropathic pain through CBR-dependent mechanisms. Additionally, emotions such as fear, anxiety, and depression are frequently experienced with neuropathic pain. Exogenous cannabinoids can mitigate these mood disorders via CBR signaling pathways. Therefore, the targeting of long-lasting ECS alterations represents a potential therapeutic approach for both neuropathic pain and emotional disorders. In this review, the long-lasting variations in neurons and glial cells in the ECS related to neuropathic pain and the accompanying emotional comorbidities are elucidated. Furthermore, the cellular and molecular mechanisms underlying synaptic plasticity and neural circuit activities in the brain are reviewed.